An Economic Analysis of Processing of Cotton Crop Produce - Radhika, E.; Kumari, R. Vijaya (International Journal of Economic Plants, 2015)
This study was conducted in 2011 covering 30 cotton growers, fifteen each commission agents and Cotton Corporation of India agents, twenty ginners and five spinners in six mandals of Adilabad and four mandals of Guntur district. Findings of the study revealed that, the average total cost of cultivation and net returns of Bt cotton was higher in Adilabad district (Rs. 69607 and Rs. 36781.15 ha-1 respectively) as compared to Guntur district (Rs. 63793.2 and Rs. 21901 ha-1 respectively). The average total cost incurred in the processing of kapas to lint and lint to yarn worked out to be ` 4630.87 and ` 17201.64 q-1 of kapas. The gross returns obtained from ginning one quintal of kapas were Rs. 4970.41, of which the returns from main product (lint) were ` 3978.81 and that from by product (seed) were Rs. 991.6. The value addition to the product in the process was ` 732.41. The net value added as a result of processing of kapas to lint was ` 339.54 q-1 ofkapas processed. The gross returns obtained from processing (spinning) of one quintal of lint were Rs. 20435, which comprised of mainly returns from yarn (Rs. 18250) and wastage (` 2185). The value addition in the process was Rs. 8435. The net value added as a result of processing of lint to yarn was Rs. 5933.36 q-1 of lint processed. The ginners have maximum financial profitability (1.86) followed by spinners (1.62) and farmers (1.39).